2019 25th International Conference on Automation and Computing (ICAC) 2019
DOI: 10.23919/iconac.2019.8895243
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive Feature Related Acoustic Emission in Grinding

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…A large number of research studies on tool condition monitoring have been reported in the literature for a variety of machining processes by measuring parameters such as force and torque, feed and spindle motor currents, acoustic emissions (AEs), vibration, cutting temperature, etc [3][4][5][6][7][8]. Of these parameters, AE has been widely used and recognized as one of the most suitable choices for grinding process monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of research studies on tool condition monitoring have been reported in the literature for a variety of machining processes by measuring parameters such as force and torque, feed and spindle motor currents, acoustic emissions (AEs), vibration, cutting temperature, etc [3][4][5][6][7][8]. Of these parameters, AE has been widely used and recognized as one of the most suitable choices for grinding process monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Karpuschewsk et al [6] investigated the influence of different dressing parameters on the AE signal, and wheel life estimation was achieved using power spectra of the enveloped AE signal. Plaza et al [7] carried out an experimental study on AE features in abrasive grinding. The AE signals were analyzed in both the time and frequency domains.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of research studies on tool condition monitoring have been reported in the literature for a variety of machining processes by measuring parameters such as force and torque, feed and spindle motor currents, acoustic emissions, vibration, cutting temperature, etc [3][4][5][6][7][8]. Of these parameters, acoustic emission (AE) has been widely used and recognised as one of the most suitable choices for grinding process monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Karpuschewski et al [7] investigated the influence of different dressing parameters on the AE signal and wheel life estimation was achieved using power spectra of the enveloped AE signal. Plaza et al [8] carried out an experimental study on acoustic emission (AE) features in abrasive grinding. The acoustic emission signals were analysed in both the time and frequency domains.…”
Section: Introductionmentioning
confidence: 99%